2000
DOI: 10.1034/j.1600-0544.2000.030203.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyoid position, pharyngeal airway and head posture in relation to relapse after the mandibular setback in skeletal Class III

Abstract: This study evaluates the process of relapse after mandibular setback surgery by an analysis of the role of craniofacial morphology, hyoid position, pharyngeal airway and head posture. Subjects examined were 62 patients who received the sagittal split ramus osteotomies (SSRO). Changes of the craniofacial and related structures were evaluated from the serial cephalograms up to 3 years after the surgery. Results indicated that mandibular relapse represented by Pg occurred mostly within 6 months after the surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
65
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 10 publications
5
65
1
3
Order By: Relevance
“…However, an aspect of orthognathic surgery that is rarely evaluated is the effect of the skeletal movements on the pharyngeal airway. Changes in airway dimensions have been demonstrated after surgical repositioning of the mandible or maxilla [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, an aspect of orthognathic surgery that is rarely evaluated is the effect of the skeletal movements on the pharyngeal airway. Changes in airway dimensions have been demonstrated after surgical repositioning of the mandible or maxilla [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The isolated mandibular setback has been the target of several studies. These studies reported a change in the position of the hyoid bone and reduction in the dimensions of the retrolingual and hypopharyngeal airway after mandibular setback surgery [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As alterações da VAS depois de cirurgia de recuo mandibular continuam controversas, com alguns estudos demonstrando que há uma diminuição das dimensões da VAS e outros mostrando que nenhuma alteração da VAS ocorre após esse tipo de cirurgia 5,10,11,12,13,14,16,18,19,21,22,23,24,25,26,27,28 . Os trabalhos em pacientes com deformidade dento-esqueléticos classe III submetidos à cirurgia ortognática demonstraram uma forte correlação entre a quantidade do movimento do recuo mandibular com o estreitamento da via aérea e alteração da posição do osso hióide.…”
unclassified